STRATEGI USTADZ DALAM PEMBINAAN AKHLAK SANTRI DI TAMAN PENDIDIKAN QUR'AN ASSA'ADAH DESA SEPINGGAN KECAMATAN SEMPARUK TAHUN 2023 - Nurfitriani; Ubabuddin Ubabuddin; Rona Rona (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research discusses the Ustadz’s strategy in develoving the morals of santri at the Assa’adah Qur’an education park, Sepinggan village, Semparuk District. The objectives of this research include the following; Firstly, knowing the application of the ustadz’s strategy in develoving the morals of santri in the Qur’an Assa’adah educational park, Sepinggan Village, Semparuk District in 2023. Second, knowing the methods used in cultivating the morals of santri in the Qur’an Assa’adah educational park, Sepinggan Village, Semparuk District in 2023.This research uses qualititative methods with descriptive methods with descriptive research type. There are three types of data collection techniques in this rearch, namely observation, interviews and dosumention. The data analysis techniques used are data collection, data reducation, data display, and drawing conclusions. Then the validity checking technique used is triangulation and member check. The result of this research show that: First, how to implement the ustadz’s strategying developing the morals of santri at the Assa’adah Qur’an education park, Sepinggan Village, Semparuk District, namely in the following way: 1) Building morals through discipline. Ustadz and Ustadzah apply rules of regulation so santri, so that they are disciplined to achieve the desired goals. 2) Moral development through supervision. Ustadz and Ustadzah implement supervision over santri by parenting and guarding santri from doing anything undesirable. Second, what methods are used in developing the morals of santri at the Assa’adah Qur’an Education Park, Sepinggan Village, Semparuk District, namely in the following ways: 1) The exemplary method, carried out by providing a good example or example to the students. Such as speaking, acting and worshiping. 2) The adcive method is carried out by conveying words that contain goodness of positive things. 3) The habituation method is carried out by providing habituation to santri to carry out good habits to be implemented. And avoid bad habits. 4) Memorization method, carried out by giving memorization to santri. Such as memorizing daily prayers, reading prayers and memorizing short surahs.